ANALISIS PERSAINGAN EKSPOR BIJI KOPI DI PASAR INTERNASIONAL - Hasibuan, M. Fariz Afif; Hendris Syah Putra (Agriprimatech, 2023)
Coffee is the main commodity in the plantation industry which has a major impact on the economy. This research aims to analyze comparative and competitive advantages in coffee production. The analytical method used is the Almost Ideal Demand System (AIDS) Model. The results of the analysis show that the price elasticity of countries such as Brazil, Colombia, Vietnam and Indonesia, which are the main source countries for coffee exports, is negative. In contrast, Honduras has positive price elasticity. Thus, if there is an increase in coffee bean exports on the global market, it is estimated that demand for coffee beans from Colombia and Honduras will increase.